Bacterial cellulose/poly(3-hydroxybutyrate) composite membranes - Barud, Hernane S. [UNESP]; Souza, Josiane L. [UNESP]; Santos, Daniele B. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2011)
Bacterial cellulose (BC)/poly(3-hydroxybutyrate) (PHB) composite membranes were prepared from chloroform-swollen BC membranes and PHB chloroform solutions. Relative contents were varied from 25 to 90 wt.% of PHB. Macroscopically homogeneous composite membranes were characterized by scanning electron microscopy, Fourier-transformed infrared spectroscopy, X rays diffraction, thermal analysis and stress-strain measurements. Depending on the relative compositions membranes coating of BC microfibrils by PHB and PHB precipitation inside the BC 3 D network of cellulose fibers could be observed. Improved mechanical properties were observed for the composites compared to the individual components suggesting potential applications for the new biodegradable materials. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Bacterial cellulose; Poly(3-hydroxybutyrate) (PHB); Green polymers